2009
DOI: 10.1161/atvbaha.108.178731
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation by Low Concentrations of Intact Oxidized LDL Particles Involves the PAF Receptor

Abstract: Objective-Mitochondrial depolarization aids platelet activation. Oxidized LDL (oxLDL) contains the medium length oxidatively truncated phospholipid hexadecyl azelaoyl-lysoPAF (HAz-LPAF) that disrupts mitochondrial function in nucleated cells, so oxLDL may augment platelet activation. Methods and Results-Flow cytometry showed intact oxLDL particles synergized with subthreshold amounts of soluble agonists to increase intracellular Ca 2ϩ , and initiate platelet aggregation and surface expression of activated gpII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 47 publications
1
56
0
2
Order By: Relevance
“…Of importance, recent studies have demonstrated that the non-PAF Ox-GPCs we measured and other Ox-GPCs chemically synthesized have significant PAF-R agonistic activity in vitro (48). It should be noted that the low amount of UVB irradiation used in the in vitro studies (600 J/m 2 ) that generates ϳ2-fold increased levels of these compounds does not generate Ox-GPCs in other cell types such as epithelial cells (28,40), which fits with the concept that the increased responsiveness of XPA-deficient cells to UVB irradiation is mediated at least in part by the resulting Ox-GPCs.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Of importance, recent studies have demonstrated that the non-PAF Ox-GPCs we measured and other Ox-GPCs chemically synthesized have significant PAF-R agonistic activity in vitro (48). It should be noted that the low amount of UVB irradiation used in the in vitro studies (600 J/m 2 ) that generates ϳ2-fold increased levels of these compounds does not generate Ox-GPCs in other cell types such as epithelial cells (28,40), which fits with the concept that the increased responsiveness of XPA-deficient cells to UVB irradiation is mediated at least in part by the resulting Ox-GPCs.…”
Section: Discussionmentioning
confidence: 90%
“…The MRM transition pairs were monitored for species previously identified as PAF receptor agonists (28,47,48) (5)oxovaleroyl-GPC (16a 5al), and 1-palmitoyl-2-glutaroyl-GPC (16a 5COOH).…”
Section: Methodsmentioning
confidence: 99%
“…21,22 Because monocytes constitutively express P-selectin glycoprotein ligand-1 (PSGL-1), OxLDL-stimulated platelets also interacted with monocytes within minutes of activation ( Figure 1A). As depicted in Figure 1B, the percentage of platelet-monocyte complexes significantly increased with the degree of oxidative modification of LDL, whereas native LDL had no effect on PMA formation.…”
Section: In Response To Oxldl Platelets Rapidly Formed Complexes Withmentioning
confidence: 99%
“…Such modifi ed phospholipids have been identifi ed in oxidized LDLs (11)(12)(13); in models of oxidative insult such as alcoholic blood ( 14 ), smokers blood ( 15 ), and electronegative LDLs ( 16 ); and in models of cutaneous infl ammation ( 17 ). Notable among these lipids are the oxidatively truncated phospholipids butanoyl/butenoyl PAF/PC ( 11 ), azelaoyl PAF/PC ( 18,19 ), palmitoyl glutaroyl PC, palmitoyl oxovaleryl PC ( 12 ), kodia PC ( 13 ), and many more ( 19 ) ( Table 1 ). Although PAF is recognized by PAF receptor (PAF-R) at subnanomolar concentrations ( 11,20 ), some of the above mentioned molecules also bind to PAF-R with barrier through juxtacrine signaling ( 34,35 ).…”
Section: Between the Substrate And Product Of Paf-ahmentioning
confidence: 99%
“…varying affi nities to activate PAF-R, hence popularly referred as PAF mimetics/PAF-like lipids ( 11,(19)(20)(21). However, these oxidized phospholipids accumulate during oxidative insult, as they are formed nonenzymatically, leading to exaggerated infl ammatory responses that are also curtailed by the action of PAF-AH ( 6,7,11 ).…”
mentioning
confidence: 99%